The Inference of Friendly Communicative Atmosphere Created by Geometric Shapes. (December 2017) - Yuasa, Masahide
Many previous studies on inference of social behaviors using geometric shapes have explored causality, animacy, intention, and desire inferred from the movements of such shapes; however, inference of communicative atmosphere in terms of friendliness/antagonism using geometric shapes has not yet been studied well. This study investigated how a friendly/antagonistic communicative atmosphere was inferred from the movement of two egg shapes. We developed animations for these shapes involving forward/backward/parallel tilts with coincidence/incoincidence of synchronous movement. Results showed significant differences in the inference of friendly/antagonistic atmosphere between coincident and incoincident synchronous movement. In addition, the inference of a friendly atmosphere was affected by the combination of forward tilt with incoincident movement, which may be interpreted as interaction between the shapes, such as responding or providing feedback. This suggests that individuals may infer a friendly/antagonistic communicative atmosphere from both coincident movement and incoincident movement interpreted as an interaction.